(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
This present work investigates the possible effect of adding the recycled nano silica waste (NS) on the workability, density, heat of hydration, and mechanical behavior and properties of industrial cement mortar. The nano silica was collected from the aluminum fluoride plant of Jordan Phosphate Mine Company. Ten mixtures of cement mortar were prepared with nano silica to cement ratios of 0%, 0.5%, 1.5%, 2%, 2.5%, 4%, 6%, 8%, and 10%. The cement mortar and NS chemical compositions are analyzed using the X-ray Fluorescence Spectrometer technique. Flow table test is adopted to examine the workability of fresh mortar specimens after mixing. The average dry and bulk densities, in addition to compressive and flexural strengths, for different concentrations of nano silica mortar samples, particularly at a duration of 28 days, have recorded a significant improvement. The results indicate an improvement in the compressive and flexural strengths as nano silica increased in the mortar mixture.